Sol-gel approach in molecular imprinting for crystal violet selective recognition - Saliza Asman,; Sharifah Mohamad,; Mohd Kamarulzaki Mustafa, (Penerbit Universiti Kebangsaan Malaysia, 2021)
A limitation of conventional MIP in thermal and mechanical stabilities condition, improper porosity and low adsorption capacity, give a reason to introduce a sol-gel method in molecular imprinting process recently. In this study, a synthesis of new sol-gel molecularly imprinted polymer (SG-MIP) was studied for crystal violet (CV) selective recognition. The control non-molecularly imprinted polymer (SG-NIP) was also synthesized as reference. The preparation of SG-MIP was introduced by a combination of the organic and inorganic mixture. The organic solution included the methacrylic acid, trimethylolpropane trimethacrylate, and benzoyl peroxide which are monomer, crosslinker, and initiator, respectively. The inorganic solution involved the ratio of tetraethyl orthosilicate: ethanol (1:1 v/v). The functional group analysis proved the successful synthesized SG-MIP and SG-NIP. The thermal analysis indicated high thermal stability for SG-MIP and SG-NIP, respectively. The morphology and surface analyses showed the respective different structures, surface, and porosity values between SG-MIP and SG-NIP, which influence the selectivity study and adsorption behaviour of SG-MIP toward CV adsorption. The result verified that the SG-MIP (4.900 mgg-1) has higher adsorption and higher selectivity characteristics compared to SG-NIP (4.432 mgg-1). The equilibrium data of kinetic and isotherm studies for SG-MIP and SG-NIP were well-fitted to the pseudo-second order model (R2 = 0.9997 and R2 = 0.9996) and Freundlich isotherm model (R2 = 0.9500 and R2 = 0.9764), respectively. The Freundlich isotherm was supported by the Scatchard plot instead of the Langmuir isotherm model.